(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To describe the changes in hand function of hemiplegia patients due to cerebral infarction and evaluate the effects of restoring hand function by electroacupuncture combined with CIMT exercises. Subjects and methods: a controlled clinical intervention on 84 patients diagnosed with hemiplegia due to cerebral infarction patients at the National Hospital of Acupuncture. Results: 100% of the studied patients had a change in motor function of the paralyzed hand, in which the frequency of loss of opposed the thumb with fingers is the highest, 94.05%. Electroacupuncture combined with CIMT exercises improves the hand function and dexterity of the paralyzed hand better than the group only treated by electroacupuncture (p<0.05). Conclusion: Using electroacupuncture combined with CIMT exercise effectively restores hand function in patients with hemiplegia due to cerebral infarction.